PENGARUH FAST FASHION TERHADAP BUDAYA KONSUMERISME DAN KERUSAKAN LINGKUNGAN DI INDONESIA - Ajriah Muazimah; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Fast fashion is a concept adopted by the clothing retailer. The direction and strategic goals of business follow the latest trend, with the best response to consumer demand through price. In the fashion industry in today's global era, the fast fashion trend is a promising market share. Affordable fashion-buying becomes common in modern societies, mainly millennials, as part of an existential effort, making society consensual. The fast fashion systems shaped by globalization inevitably have varying impacts, one of which is environmental damage.The author's type of research is a deductive qualitative study using deductive library research with an analytical description. Data collection techniques are done through field studies, library studies, documents, interviews, and primary and secondary. The theory and perspective the writer uses is constructivism with the level of analysis of the international system.This research shows that the dependence on polyester materials has made the fashion industry one of the world's highest polluters because of emissions from nonbiodegradable production and waste. Polyester material in clothes has produced sewage that is potentially harmful to the water environment and carries bacteria that are harmful to humans. The trade was also responsible for ecological damage in several key sources. Besides being a source of life for humans, water has become a significant force in the clothing industry. However, the fact remains that rivers in some countries are polluted by waste-waste waste cloth dyeing. The selin, a badly sought-after fashion product, will be discarded and becomes very difficult for recycling garbage.Key Words : Fast Fashion, a Consumeristic Culture, Globalization and Modernity Stream, Environmental Damage.